The Role of The West Java Police (Polda Jabar) As Gatekeepers In Restorative Justice In Relation To Police Regulation No. 8 Of 2021 on Restorative Justice - Ra'afi Nur Azhami, Mochammad; Mayaningsih, Dewi; Kurniawan, Wawan (Journal of Social Research, 2025)
This study aims to analyze the effectiveness of restorative justice in reducing case accumulation within the Indonesian National Police (POLRI), identify challenges in its implementation, and propose solutions for its integration into the legal system. Restorative justice, as regulated in National Police Chief Regulation Number 8 of 2021, seeks to resolve conflicts between violators, victims, and the community while alleviating the burden on courts and correctional institutions. This research employs an analytical descriptive method with an empirical juridical approach, collecting data through observations, interviews, and document studies. The findings indicate that while restorative justice offers a potential solution to case backlog issues, its implementation remains hindered by procedural complexity, limited expertise among police personnel, and the absence of a dedicated legal framework regulating its execution. Additionally, the misalignment between restorative justice within the police force and other law enforcement agencies further complicates its effectiveness. The study concludes that overcoming these challenges requires enhancing human resource capacity within the police, fostering public awareness of restorative justice principles, providing specialized training for investigators, and advocating for the establishment of a Criminal Procedure Code that formally regulates restorative justice mechanisms to ensure consistency and alignment across all legal institutions.